Neurophysiological evidence of efference copies to inner speech - Whitford, Thomas J; Jack, Bradley N; Pearson, Daniel; Griffiths, Oren; Luque, David; Harris, Anthony WF; Spencer, Kevin M; Le Pelley, Mike E (eLife, 2017)
Efference copies refer to internal duplicates of movement-producing neural signals. Their primary function is to predict, and often suppress, the sensory consequences of willed movements. Efference copies have been almost exclusively investigated in the context of overt movements. The current electrophysiological study employed a novel design to show that inner speech – the silent production of words in one’s mind – is also associated with an efference copy. Participants produced an inner phoneme at a precisely specified time, at which an audible phoneme was concurrently presented. The production of the inner phoneme resulted in electrophysiological suppression, but only if the content of the inner phoneme matched the content of the audible phoneme. These results demonstrate that inner speech – a purely mental action – is associated with an efference copy with detailed auditory properties. These findings suggest that inner speech may ultimately reflect a special type of overt speech.
Keywords: corollary discharge; efference copy; inner speech; covert speech; sensory attenuation